Self-Compassion, Social Connectedness And Self-Regulation Of Health Behaviour: A Preliminary Study On Local Undergraduates In Malaysia - Ying, Kelvin; Mohd Hashim, Intan Hashimah (2016)
Self-compassion refers to the ability to care and have compassion towards oneself during the hard time in their life, which offers them a sense of warmth, connectedness and concern. Social connectedness refers to how individuals relate themselves with others and how they perceive themselves in those relationships. Self-regulation of health behaviour refers to one’s initiatives, such as setting goals, taking action and monitoring progress, in personal health management. This study examined 1) gender difference in self-compassion, 2) the level of self-compassion, social connectedness and self-regulation of health behaviour, and 3) the relationship between self-compassion, social connectedness and self-regulation of health behaviour, among local undergraduates in Malaysia. Participants were 292 local undergraduates in a Malaysian public university who completed a questionnaire package on Self-Compassion Scale (α = .79), the Health Responsible part of Health-Promoting Lifestyle Profile II (α = .85) and The Social Connectedness Scale-Revised (α = .87). Findings reported insignificant gender difference in self-compassion among local undergraduates. Findings also reported adequate level of self-compassion, high level of social connectedness and low level of self-regulation of health behaviour among local undergraduates in Malaysia. There was significant and positive relationship between self-compassion, social connectedness and self-regulation of health behaviour. Contribution, limitation and future research direction of current study were discussed.